Development and implementation of Intelligent Soot Blowing Optimization System for TNB Janamanjung - Sundaram T.; Basim Ismail F.; Gunnasegaran P.; Gurusingam P. (EDP Sciences, 2023)
Backpropagation; Boilers; Coal; Computational fluid dynamics; Fossil fuel power plants; Neural networks; Soot; Coal-fired power plant; Combination of neural-network; Data preparation; Energy demands; Optimization system; Predictive tools; Training algorithms; Training function; Dust